Recht in der Krise APARIUZ XXIII - Bernet, Sandro (sui generis Verlag, 2022)
How does the law react to real crises and what is the problem-solving power of legal regulation in difficult situations? Conversely, do crises also have an impact on how the law works - and should they have one at all? In the XXIII. Volume of the APARIUZ publication series, young researchers from the University of Zurich from different legal areas deal with how the law deals with crises. The starting point for reflections on the interplay between crises and law is not only the corona pandemic, but also a wide variety of other situations that encourage - or force - criticism and rethinking.